Red blood cells induce endothelial dysfunction in patients with ST-elevation myocardial infarction and elevated C-reactive protein. (3rd October 2022) - Tengbom, J; Collado, A; Jiao, T; Yang, J; Zhou, Z; Mahdi, A; Pernow, J
Abstract: Background: The important role of inflammation in atherosclerotic plaque progression and instability leading to myocardial infarction has been widely demonstrated. C-reactive protein (CRP) has been shown to be of predictive value in atherosclerotic cardiovascular disease. The red blood cell (RBC) is an important regulator of cardiovascular function through nitric oxide bioactivity and oxidative stress in ischemic heart disease. Also, arginase-1 has been shown to greatly influence nitric oxide bioactivity in RBCs and to cause endothelial dysfunction. However, the mechanisms by which RBCs regulate vascular function in patients with myocardial infarction and its relation to inflammation and arginase-1 remain unknown. Objective: The study aimed to investigate the effect of RBCs on endothelial function in patients with ST-elevation myocardial infarction (STEMI) and its possible association with systemic inflammation and arginase-1. Material and methods: Blood samples were collected from patients with STEMI within 36 h after admission and from age-matched healthy controls. RBCs were incubated with isolated rat aortic segments for 18 h after which the aortas were assessed for endothelium-dependent and endothelium-independent relaxations using wire myographs and application of acetylcholine and nitroprusside, respectively. The vascular response was evaluated in relation to the level of inflammation defined as CRP <2 and ≥2 mg/L at admission. The levels of 4-hydroxynonenal (4-HNE; a marker of oxidative stress formed by lipid peroxidation) and the expression of arginase-1 were visualized in rat aortas following incubation with RBCs by immunohistochemistry. All handling and procedures regarding human subjects and sampling were performed according to the Declaration of Helsinki. All animal experiments and procedures were performed according to the guidelines by the U.S National Institutes of Health (NIH publication no 85–23, revised 1996). Results: RBCs from patients with STEMI and elevated CRP (≥2 mg/L, mean of 9.6 mg/L) induced significant impairment of endothelium-dependent relaxation compared to RBCs from patients with STEMI and low CRP (<2 mg/L, mean of 1.0 mg/L) and to the healthy controls (Fig. 1). Endothelium-independent relaxations did not differ between the groups. Immunohistochemical staining of the aorta revealed that incubation with RBCs from patients with STEMI and high CRP increased the expression of 4-HNE and arginase-1 compared to incubation of RBCs from healthy controls and patients with STEMI and low CRP (Fig. 2). Conclusion: RBCs from patients with STEMI and elevated CRP induce endothelial dysfunction and increase the expression of 4-HNE and arginase-1, indicating that inflammation is involved in the mechanism by which RBCs induce endothelial dysfunction in STEMI. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Lung foundation